International cooperation of the Kabardino-Balkarian Republic in the field of economics in the first half of the 90s of the XX century - Marina V., Zhanokova (Kavkazologiya, 2024)
In the first half of the 1990s, post-Soviet Russia experienced large-scale transformations of state, socioeconomic, and institutional legal structures, which had a substantial impact on the country’s and the world’s entire economic and legal environment. Because of the transformations that took place, there was a general attitude towards integration into the global market, liberalization of the complex of public relations, including the formation of a certain degree of “independence” of the country’s subjects in the decision-making process, granting the latter greater rights and freedoms in foreign economic activity. Under the current conditions, the Government of the Kabardino-Balkarian Republic attempted establish as many contacts as possible with several countries in the field of trade and economic cooperation, using any opportunities for interaction with the leader-ship of other states, as well as with representatives of individual foreign firms and business cir-cles. This had its positive results, since in the analyzed period several joint Russian-foreign com-panies appeared on the territory of the Kabardino-Balkarian Republic, foreign investments were attracted to the republic for the development of certain industries, and the states began to view the Kabardino-Balkarian Republic as a promising economic partner. However, the study of the histor-ical and statistical material of the foreign economic activity of the Kabardino-Balkarian Republic in the first half of the 90s of the XX century made it possible to identify barriers and threats that did not allow the full use of the internal potential and capabilities of the republic, including: im-perfection of the legislative framework, customs and tax regulation, lack of a developed credit and financial system, inconsistency of actions of federal and regional authorities on certain issues of international cooperation, unfavorable political situation on the North Caucasus.